Transmission and Transformation of Kabbalistic Knowledge in Italy at the End of the Fifteenth Century - Buzzetta, Flavia (European journal of jewish studies, 2022)
The article looks at the transfer of knowledge between Judaism and Christianity in the Renaissance, a period characterized by the encounter of different cultures and belief systems. In particular, it will focus on the Christian Kabbalah, which channels various philosophical and sapiential traditions into a universal, and at the same time, plural vision of wisdom. This convergence of ideas resulted, on the one hand, in the elaboration of translations, adaptations, and vulgarization of Jewish texts and, on the other, in the development of new interpretations. This is a characteristic of the collected writings of Pierleone of Spoleto, which involved the transformative communication of Jewish translators and the creative reception of Christian humanists. Of these manuscripts, we will examine the annotations concerning the sefirot, which are an excellent example of the reinterpretation of Jewish thought through a typically humanistic perspective.